Investigation on Ash Slagging Characteristics During Combustion of Biomass Pellets and Effect of Additives - Wang, L.; Skjevrak, G.; Skreiberg, Ø.; Wu, Hongwei; Nielsen, H.; Hustad, J. (American Chemical Society, 2018)
This study reports a systematic investigation into ash slagging behavior during combustion of barley straw and barley husk pellets with or without additives in a residential pellet burner. The slagging tendencies of the pellets were evaluated based on the amount, chemistry, mineralogy, and morphology of inlet ash formed as slag and sintering degrees of residual ash. The barley straw and husk pellets showed high slagging tendencies with 39 and 54 wt % ingoing ash formed as slag. Analyses using X-ray fluorescence and scanning electron microcopy combined with energy-dispersive X-ray spectroscopy revealed high concentrations of K, Si, and Ca but a minor amount of P in barley straw slag. The slag mainly contained melted potassium silicates directly observed by X-ray diffraction. For the barley husk, high ash slagging tendency was observed and mainly attributed to the formation and melting of potassium phosphates, potassium silicates, and complex mixtures of the two mineral phases. Addition of marble sludge completely eliminated ash slagging during combustion of barley straw and husk pellets because it led to the formation of high temperature melting calcium potassium phosphates, calcium rich potassium silicates, and oxides. Addition of calcium lignosulfonate showed a less pronounced ability to mitigate ash slagging issues during pellet combustion, although it promoted the formation of calcium-rich silicates and phosphates (both with high-melting points) in barley straw and husk ash, respectively. This process was accompanied by considerable reduction in the amount and sintering degree of the formed barley straw and husk slag.